Spatial deciphering of the transcriptomic heterogeneity of tumor spread through air spaces in lung cancer - Wang, Wenhao; Zhou, Wenhao; Fan, Jingli; Jiang, Tao; Yang, Guang; Song, Congcong; Xu, Siwei; Luo, Haitao; Liu, Huining (Frontiers in Pharmacology, 2025)
BackgroundSpread through air spaces (STAS) represents a novel invasion mechanism in adenocarcinoma that considerably influences lung cancer clinical outcomes; however, studies of its mechanisms at the spatial level are lacking.MethodsWe used the NanoString GeoMx digital spatial profiling (DSP) technology to conduct a spatial transcriptomic analysis of surgically resected tissues from non-small-cell lung cancer (NSCLC) patients with or without STAS.ResultsCompared with tumor nests in non-STAS patients, HLA-DRB5 and RASGRF1 were significantly less expressed in compartments of STAS, suggesting their inhibitory roles in the occurrence of STAS. Meanwhile, an increase in CD4 T memory cells and a decrease in B cells were observed in the tumor immune microenvironment of STAS. Furthermore, distinct molecular profiles were observed between tumor cells in tumor nests and in air spaces in STAS patients, which was highlighted by the elevated ITGA2 expression in the air spaces. These results were validated in an independent cohort by multiplex immunofluorescence stainings.ConclusionThis study is the first to use DSP to analyze spatial transcriptomic profiles of NSCLC tumor nests and air space tumors, and it identifies potential module features that may be used for STAS identification and prognosis.